2021
DOI: 10.1503/cjs.013019
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and survival among patients with colorectal cancer before the age of screening: a systematic review and meta-analysis

Abstract: Background: The incidence of colorectal cancer in North America is rising among patients younger than 50 years. Available data are conflicting regarding presentation and outcomes in this population. This review aimed to synthesize literature regarding young patients with colorectal cancer with respect to patient demographics, disease extent and survival, compared with patients older than 50 years. Methods: We searched Medline, Embase, the Cochrane Central Register of Controlled Trials and PubMed for articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Despite an overall mortality rate of 31% over a mean follow-up period of 3.9 years, our Kaplan–Meier regression did show better overall and cancer-specific survival in younger patients with CRC, compared with older patients. This is consistent with a recent systematic review by Griffiths and colleagues, 17 which found that young patients with CRC in North America have improved survival when controlling for cancer stage. It remains unclear if this survival benefit is owing to the ability of young patients to tolerate more aggressive treatment practices or differing cancer biology.…”
Section: Discussionsupporting
confidence: 91%
“…Despite an overall mortality rate of 31% over a mean follow-up period of 3.9 years, our Kaplan–Meier regression did show better overall and cancer-specific survival in younger patients with CRC, compared with older patients. This is consistent with a recent systematic review by Griffiths and colleagues, 17 which found that young patients with CRC in North America have improved survival when controlling for cancer stage. It remains unclear if this survival benefit is owing to the ability of young patients to tolerate more aggressive treatment practices or differing cancer biology.…”
Section: Discussionsupporting
confidence: 91%
“…7 Support for a younger age at onset for screening was initially based on a recognition that the incidence of CRC among patients younger than 50 years has increased 8,9 and that it is often being diagnosed in advanced stages owing, in part, to diagnostic delays. 10 While the incidence of CRC among patients aged 40 to 49 years is lower than among those 50 years or older, these data are influenced by lead-time bias given differential screening and diagnostic colonoscopy rates, such that the CRC risk of younger cohorts is actually greater than many patients and clinicians may realize.…”
mentioning
confidence: 99%
“…This echoes a departure from long-standing prior recommendations from many sources recommending average-risk screening to begin at age 50 years, and advocacy for earlier age at onset for screening is one that is also supported by organizations such as the American Cancer Society and the American Society of Colon and Rectal Surgeons . Support for a younger age at onset for screening was initially based on a recognition that the incidence of CRC among patients younger than 50 years has increased and that it is often being diagnosed in advanced stages owing, in part, to diagnostic delays . While the incidence of CRC among patients aged 40 to 49 years is lower than among those 50 years or older, these data are influenced by lead-time bias given differential screening and diagnostic colonoscopy rates, such that the CRC risk of younger cohorts is actually greater than many patients and clinicians may realize.…”
mentioning
confidence: 99%
“…one study investigated crc treatment outcomes in younger individuals that were not included in the screening process. on average, these patients presented with more advanced disease and poorly differentiated histology (higher TNM grade) (39). one could argue that early-onset crc has a more aggressive clinical presentation.…”
Section: Discussionmentioning
confidence: 94%